2020
DOI: 10.1111/csp2.195
|View full text |Cite
|
Sign up to set email alerts
|

Is seabird light‐induced mortality explained by the visual system development?

Abstract: Seabirds are impacted by coastal light pollution, leading to massive mortality events. Juveniles comprise the majority of affected individuals, while adults are only seldom grounded and reported in rescue programs. We propose a connection between visual system development of burrow nesting seabirds and the observed higher vulnerability to light pollution by a specific age group. We illustrate the need for multidisciplinary research to better understand and further mitigate light-induced mortality. K E Y W O R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
1
20
0
2
Order By: Relevance
“…Around 10% of birds collected in the campaigns die before release back to the wild, although light-induced mortality could be higher as laypeople do not usually report dead birds, thus 40% is possibly a more accurate estimate (Podolskyi et al, 1998;Ainley et al, 2001;Rodríguez et al, 2014). Why petrels become disorientated by lights is far from being fully understood (Atchoi et al, 2020). The majority of our knowledge about the fallout comes from observational data from rescue campaigns and mainly consists of the reporting of species identification, individual numbers, dates, and locations (Rodríguez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Around 10% of birds collected in the campaigns die before release back to the wild, although light-induced mortality could be higher as laypeople do not usually report dead birds, thus 40% is possibly a more accurate estimate (Podolskyi et al, 1998;Ainley et al, 2001;Rodríguez et al, 2014). Why petrels become disorientated by lights is far from being fully understood (Atchoi et al, 2020). The majority of our knowledge about the fallout comes from observational data from rescue campaigns and mainly consists of the reporting of species identification, individual numbers, dates, and locations (Rodríguez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This difference could potentially be caused by differences in the developmental stage of the birds’ eyes. It has been suggested that the eyes of young burrow-nesting seabirds, as well as hatchling marine sea turtles, are not fully developed upon leaving the nest, thus possibly resulting in attraction towards light 53 , 54 . Avoidance of light may develop later over the animals’ lifetime and as their eyes finish development, but the mechanisms underlying this remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, adult seabirds may be more vulnerable to offshore ALAN during the courtship or chick‐rearing stage when seabirds visit their breeding colonies more regularly, compared to the incubation stage, when commuting is limited as birds are brooding eggs (Taylor et al, 2020). Fledging juveniles have been shown to be more vulnerable to offshore ALAN than adults (Atchoi et al, 2020; Rodríguez et al, 2014). Understanding inter‐annual patterns in dynamic threats such as offshore ALAN is equally important.…”
Section: Introductionmentioning
confidence: 99%